Identification of an acid sphingomyelinase ceramide kinase pathway in the regulation of the chemokine CCL5 - Newcomb, Benjamin; Rhein, Cosima; Mileva, Izolda; Ahmad, Rasheed; Clarke, Christopher J.; Snider, Justin; Obeid, Lina M.; Hannun, Yusuf A. (Journal of Lipid Research, 2018)
Acid sphingomyelinase (ASM) hydrolyzes sphingomyelin to produce the biologically active lipid ceramide. Previous studies have implicated ASM in the induction of the chemokine CCL5 in response to TNF-α however, the lipid mediator of this effect was not established. In the present study, we identified a novel pathway connecting ASM and ceramide kinase (CERK). The results show that TNF-α induces the formation of ceramide 1-phosphate (C-1-P) in a CERK-dependent manner. Silencing of CERK blocks CCL5 production in response to TNF-α. Interestingly, cells lacking ASM have decreased C-1-P production following TNF-α treatment, suggesting that ASM may be acting upstream of CERK. Functionally, ASM and CERK induce a highly concordant program of cytokine production and both are required for migration of breast cancer cells. Taken together, these data suggest ASM can produce ceramide which is then converted to C-1-P by CERK, and that C-1-P is required for production of CCL5 and several cytokines and chemokines, with roles in cell migration. These results highlight the diversity in action of ASM through more than one bioactive sphingolipid.
EVALuna2:211706